A new simple shear deformation plate theory. (1st July 2017) - Thai, Huu-Tai; Nguyen, Trung-Kien; Vo, Thuc P.; Ngo, Tuan
Abstract: This paper proposes a new simple shear deformation theory for isotropic plates. The present theory involves one unknown and one governing equation as in the classical plate theory, but it is capable of accurately capturing shear deformation effects. The displacement field of the present theory was based on a two variable refined plate theory in which the transverse displacement is partitioned into the bending and shear parts. Based on the equilibrium equations of three-dimensional (3D) elasticity theory, the relationship between the bending and shear parts was established. Therefore, the number of unknowns of the present theory was reduced from two to one. Closed-form solutions were presented for both Navier- and Levy-type plates. Numerical results indicate that the obtained predictions are comparable with those generated by ABAQUS and available results predicted by 3D elasticity theory, first-order and third-order shear deformation theories.